Spatialities of urban change : selected themes from Bloemfontein at the beginning of the 21st century - Marais, Lochner; Visser, Gustav (Sun Press, 2008)
It is against a post-colonial backdrop that the collection of essays assembled in this book aims to make a contribution to understanding the realities of urban centres which feature less frequently in the academic press. The research reported in this collection echoes and highlights many of the themes found in both urban theory derived from the realities of many?world cities?, and the challenges remarked upon in development theory seen in much of the work focused on South Africa?s main metropolitan regions.